A case study on the consecration of space at Mahidol University Salaya Campus - Dillon, Jane (Poligrafi, 2022)
This article presents the phenomenon of religious revival in the twentieth cen-tury through a case study of phenomenology at Mahidol University Salaya cam-pus, Thailand. The principal scope of this study is on the socio-religious construct of the contemporary Buddhist community at Mahidol University Salaya campus. The revival of religion at the university has transformed the campus into a religious space that juxtapositions its secular academic framework.
Keywords: case studies; duh; profane; religije; religion; sacred spirit; sveto; študije primera; Tajska; tajska religija; Thai religion; Thailand